Evidence that distinct human primary motor cortex circuits control discrete and rhythmic movements - Wiegel, Patrick; Kurz, Alexander; Leukel, Christian (The Journal of physiology, 2020)
Key points Discrete and rhythmic dynamics are inherent components of (human) movements. We provide evidence that distinct human motor cortex circuits contribute to discrete and rhythmic movements. Excitability of supragranular layer circuits of the human motor cortex was higher during discrete movements than during rhythmic movements. Conversely, more complex corticospinal circuits showed higher excitability during rhythmic movements than during discrete movements. No task‐specific differences existed for corticospinal output neurons at infragranular layers. The excitability differences were found to be time(phase)‐specific and could not be explained by the kinematic properties of the movements. The same task‐specific differences were found between the last cycle of a rhythmic movement period and ongoing rhythmic movements. Human actions entail discrete and rhythmic movements (DM and RM, respectively). Recent insights from human and animal studies indicate different neural control mechanisms for DM and RM, emphasizing the intrinsic nature of the task. However, how distinct human motor cortex circuits contribute to these movements remains largely unknown. In the present study, we tested distinct primary motor cortex and corticospinal circuits and proposed that they show differential excitability between DM and RM. Human subjects performed either 1) DM or 2) RM using their right wrist. We applied an advanced electrophysiological approach involving transcranial magnetic stimulation and peripheral nerve stimulation to test the excitability of the neural circuits. Probing was performed at different movement phases: movement initiation (MI, 20 ms after EMG onset) and movement execution (ME, 200 ms after EMG onset) of the wrist flexion. At MI, excitability at supragranular layers was significantly higher in DM than in RM. Conversely, excitability of more complex corticospinal circuits was significantly lower in DM than RM at ME. No task‐specific differences were found for direct corticospinal output neurons at infragranular layers. The neural differences could not be explained by the kinematic properties of the movements and also existed between ongoing RM and the last cycle of RM. Our results therefore strengthen the hypothesis that different neural control mechanisms engage in DM and RM. Key points Discrete and rhythmic dynamics are inherent components of (human) movements. We provide evidence that distinct human motor cortex circuits contribute to discrete and rhythmic movements. Excitability of supragranular layer circuits of the human motor cortex was higher during discrete movements than during rhythmic movements. Conversely, more complex corticospinal circuits showed higher excitability during rhythmic movements than during discrete movements. No task‐specific differences existed for corticospinal output neurons at infragranular layers. The excitability differences were found to be time(phase)‐specific and could not be explained by the kinematic properties of the movements. The same task‐specific differences were found between the last cycle of a rhythmic movement period and ongoing rhythmic movements.